2018
DOI: 10.1007/978-3-030-03023-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Student Drop-Out Rates Using Data Mining Techniques: A Case Study

Abstract: The prevention of students dropping out is considered very important in many educational institutions. In this paper we describe the results of an educational data analytics case study focused on detection of dropout of Systems Engineering (SE) undergraduate students after 6 years of enrollment in a Colombian university. Original data is extended and enriched using a feature engineering process. Our experimental results showed that simple algorithms achieve reliable levels of accuracy to identify predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…To estimate the probability of new university students failing throughout their learning process, AI applications can be employed as such (Wu, Chen, & Tsai, 2018). There have been several attempts (e.g., Abu Zohair, 2019;Hew, Hu, Qiao, & Tang, 2020;Pérez, Castellanos, & Correal, 2018) to predict student performance or dropout using algorithms in higher education research in order to help at-risk students by assuring their retention. For instance, to predict students' performance in a university course, Abu Zohair (2019) used clustering algorithms and a small dataset for training and model construction, establishing a reliable and accurate prediction model with a prediction accuracy of approximately 70%.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the probability of new university students failing throughout their learning process, AI applications can be employed as such (Wu, Chen, & Tsai, 2018). There have been several attempts (e.g., Abu Zohair, 2019;Hew, Hu, Qiao, & Tang, 2020;Pérez, Castellanos, & Correal, 2018) to predict student performance or dropout using algorithms in higher education research in order to help at-risk students by assuring their retention. For instance, to predict students' performance in a university course, Abu Zohair (2019) used clustering algorithms and a small dataset for training and model construction, establishing a reliable and accurate prediction model with a prediction accuracy of approximately 70%.…”
Section: Introductionmentioning
confidence: 99%
“…P´erez et al [17] presented their initial results that prediction of attrition of students from a large dataset of Systems Engineering (SE) undergraduate students after six years of registration at a Colombian university, the dataset includes 762 students. In their study, they applied four algorithms which are Decision Tree, Random Forest, Naive Bayes and Logistic Regression.…”
Section: Related Workmentioning
confidence: 99%
“…The work showed that the accuracy of the naïve bayes classification technique is more prominent than another algorithm. P´erez et al [14], illustrated the results of an educational data analytics case study concentrated on the dropout detection of systems engineering undergraduate students after six years of enrollment. Primary data is prolonged and improved using an engineering process which is known as a feature engineering process.…”
Section: Literature Reviewmentioning
confidence: 99%